The antibiotic de-escalation strategy in patients with multidrug-resistant bacterial colonization after allogeneic stem cell transplantation - Bono, Roberto; Sapienza, Giuseppe; Tringali, Stefania; Rotolo, Cristina; Santoro, Alessandra; Di Noto, Laura; Pirrera, Angelo; Schirò, Floriana; Rubino, Raffaella; Cascio, Antonio; Siragusa, Sergio; Tommaselli, Carmen; et al. (Frontiers in Microbiology, 2025)
Colonization by multidrug-resistant (MDR) bacteria and related bloodstream infections (BSI) are associated with a high rate of mortality in patients with hematological malignancies after intensive chemotherapy and allogeneic stem cell transplantation (allo-SCT). In this retrospective study, we analyzed the outcomes of patients colonized with MDR bacteria (primarily carbapenem-resistant klebsiella pneumoniae, KPC), before allo-SCT. We also investigated the feasibility and safety of an antimicrobial de-escalating approach in these patients. Since 2021, 106 patients have been undergoing allo-SCT in our department, and 34 (32%) of them were colonized by MDR bacteria before allo-SCT. In the pre-engraftment period, 84% received an empiric antibiotic therapy (EAT) active against MDR bacteria and 16% were treated with a conventional EAT. The MDR translocation rate was null, and the overall de-escalation rate was 79%, with 75% in patients with fever of unknown origin (FUO). Among the cohort of patients with MDR-positive rectal swabs just before allo-SCT (n = 18), the de-escalation rate was 100%. The all-cause mortality rates at 30 and 100 days for the whole MDR patient population were 6% (2/34) and 12% (4/34), respectively. Day +30 infection-related mortality rate was 3%. In this study, we confirm the safety of the de-escalation approach in patients with previous MDR infection after allo-SCT. This could reduce the exposure time to EAT antibiotics, reducing the selective pressure.